Dark beyond darkness the Cuban Missile Crisis as history, warning, and catalyst - Blight, James G. 1946-; Lang, Janet M. 1948- (Rowman & Littlefield, 2018)
"Dark Beyond Darkness is the first book to take readers deeply inside the experience and calculations of leaders during the Cuban Missile Crisis and to connect that crisis to the nuclear risk today, whether from war between superpowers, climate catastrophe following a regional nuclear war or a nuclear conflict sparked by an accident."...Provided by publisher
Includes bibliographical references and index
Keywords: Cuban Missile Crisis, 1962; Nuclear disarmament; Nuclear warfare -- Prevention; Cuban Missile Crisis, 1962 -- Influence; Nuclear crisis control -- Case studies; Kubakrise; Kernwaffe